Volume Change Measurements Using 2D DIC System - Kotlanova, Barbora; Javorik, Jakub; Zaludek, Milan; Ogunleye, Raphael Olabanji (Manufacturing Technology Journal, 2023)
The presented study focuses on measuring volume changes in elastomeric materials using digital image correlation (DIC), specifically the 2D DIC universal system and the 2D DIC video-extensometer directly implemented to the universal testing machine. Optical measurement methods were applied in two-dimensional (2D) configurations during the mechanical testing of dumbbell-shaped test specimens under uniaxial tension. The measured data were used to determine the dependencies of the bulk modulus and Poisson's ratio on the strain. The dependencies obtained by both methods correspond to the model behavior of rubber-like materials. Compared to the 2D DIC implemented video-extensometer, the 2D DIC universal system provides a tool for measuring transverse and longitudinal strain, and a wide range of post-processing options, including change of the input parameters, settings, or calculation relations.
Keywords: Elastomer; DIC; Volume Change; Bulk Modulus; Poisson's ratio